A profile of children with traumatic brain injury admitted to the Red Cross War Memorial Children?s Hospital Paediatric Intensive Care Unit in Cape Town, South Africa, between 2015 and 2019 - Du Plooy, Elri (Department of Paediatrics and Child Health, 2024)
A Profile of Children with Traumatic Brain Injury Admitted to the Red Cross War Memorial Children's Hospital Paediatric Intensive Care Unit in Cape Town, South Africa, between 2015 and 2019 Background: Paediatric traumatic brain injury (TBI) is a public health problem with high morbidity and mortality. Objectives: We aim to highlight risk factors and describe associated morbidity and mortality of children admitted to our Paediatric Intensive Care Unit (PICU) at Red Cross War Memorial Children's Hospital in Cape Town. Methods: We retrospectively documented the hospitalization of all children with TBI admitted into our PICU between 2015 and 2019. Results: Of 272 children identified, 232 were enrolled: 190 (81.9%) had severe TBI (Glasgow Coma Scale [GCS] ≤8), 32 (13.8%) moderate TBI (GCS 9-12) and 10 (4.3%) mild TBI (GCS ≥13). Median age was 6.5 (IQR 3.5-9) years; 144 (62.1%) were male. Motor vehicle accidents accounted for 77% (179) of injuries. Two hundred (86.2%) children were invasively ventilated for a median of 3.5 (IQR 1-7) days; 26 children (13%, n=200) had a failed extubation and 16/200 (8%) required tracheostomies. Ninety-eight children (42.2%) had intracranial pressure monitoring. Almost 30% (67/232) required vasopressor support. Approximately a third (83/232) developed trauma-related seizures; 25 children (10.8%) required a Thiopentone infusion and 9 children (3.9%) a decompressive craniectomy. Common complications were post-extubation stridor (29/200 [14.5%]), hemiparesis (20/232 [8.6%]) and diabetes insipidus (15/232 [6.5%]). Median PICU stay was 3 (IQR 1-8.3) days, and hospitalization 11 (IQR 5-20) days. Eighty- three (35.8%) children were transferred for further rehabilitation; 24 (10.3%) died. Conclusion: Despite marked improvement since the 1990's, children admitted to PICU with TBI had considerable morbidity and mortality. Enhanced primary preventative strategies, especially for motor vehicle accidents, are imperative to prevent TBI in children.